2022
DOI: 10.3727/152599521x16288665119413
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Congestion in Australian Running Events: An Analysis from The Perspective of Race Directors

Abstract: This qualitative study aimed to examine the views of Australian race directors regarding the prevalence of congestion and its impact on runners during running events. Five race directors who organise large running events in Australia were interviewed in a focus group setting. Thirty-five Australian race directors also completed an electronic survey examining their experiences with congestion during running events they organise. Similar themes emerged from findings gathered in the focus group and survey. Race d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In turn, most of these survey respondents (73%) indicated that their experiences with congestion had impacted their event satisfaction, with many (47%) highlighting that race congestion (via previous experience or feedback from others) has led to them not participating in an event [5]. Indeed, race directors acknowledge that runner congestion negatively impacts the safety and satisfaction of participants during the events they organize and emphasize the need for guidelines to be established that help them manage runner congestion [4]. Accordingly, this study provides an initial source of evidence to support the development of such guidelines regarding the use of control strategies that may subsequently improve runner congestion during running events.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In turn, most of these survey respondents (73%) indicated that their experiences with congestion had impacted their event satisfaction, with many (47%) highlighting that race congestion (via previous experience or feedback from others) has led to them not participating in an event [5]. Indeed, race directors acknowledge that runner congestion negatively impacts the safety and satisfaction of participants during the events they organize and emphasize the need for guidelines to be established that help them manage runner congestion [4]. Accordingly, this study provides an initial source of evidence to support the development of such guidelines regarding the use of control strategies that may subsequently improve runner congestion during running events.…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding, or runner congestion, during running events, can potentially cause injuries to participants via slips, falls, being trampled, and being crushed [2,3]. In this regard, survey data provided from 35 race directors with experience coordinating large running events in Australia indicated that almost half of the respondents (43%) had received feedback from runners related to congestion during their events, with this feedback mostly related to the impacts of congestion on runner satisfaction (94%) and safety (62%) [4]. Likewise, survey data from 222 runners who have participated in running events indicated most of them had experienced congestion when waiting for race commencement (93%), as the race commenced (97%), and on-course during the race (88%), with their experiences encountering congestion "somewhat" to "extremely" impacting (i.e., rating of at least 3 on a 5-point Likert item) their satisfaction (73%) and safety (43%) during the event [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations